Modeling and calculation of thermal and photophysical characteristics of high-performance silicon solar cells - Chuchvaga, N.A.; Aimaganbetov, K.P.; Tokmoldin, N.S.; Tokmoldin, S.Zh. (Recent Contributions to Physics, 2019)
In order to study and compare the physical characteristics of high-performance silicon solar cells with mono- and bifacial generation of carriers, calculations were made of the temperature field distribution and light propagation in cells having a standard architecture of heterostructure silicon solar cell based on the "amorphous silicon-crystalline silicon" junction, also known as HIT. It has been shown that in comparison with a monofacial solar cell, a bifacial cell is less susceptible to heating. At the same time, the amount of light penetrating into the bifacial solar cell exceeds the amount of light penetrating into the monofacial cell, due to the presence of albedo at the level of 17%. The possibility of photovoltaic conversion of albedo radiation plays an important role in increasing the total power generation in bifacial solar cells and demonstrates their significant advantage over monofacial photovoltaic converters.